Implementasi Transport Layer Security dengan Algoritma AES Pada Jaringan IoT Menggunakan Protokol MQTT - Azwar, Hamid; Gary, Felix (Politeknik Caltex Riau, 2025)
Data security is a crucial aspect in the era of Industry 4.0, where nearly all technologies are based on the Internet of Things (IoT). According to recent reports, while security advancements in software and hardware computing have shown progress in recent years, the security level of IoT devices remains lagging. To address this issue, this study proposes a solution by securing IoT devices through the implementation of TLS (Transport Layer Security) with the AES algorithm using the MQTT (Message Queuing Telemetry Transport) protocol. This research aims to ensure data integrity during communication and prevent data theft by encrypting transmitted data, rendering it inaccessible to unauthorized parties. The testing was conducted by comparing parameters such as RAM (Random Access Memory) usage, CPU (Central Processing Unit) usage on the ESP32 device, and communication delay. The results show that the TLS implementation resulted in an average remaining RAM of 180,256 bytes out of 520 KB, CPU usage of 0.53% out of 240 MHz, and a communication delay of 0.475 seconds. In comparison, without TLS implementation, the average remaining RAM was 224,825 bytes out of 520 KB, CPU usage was 0.2% out of 240 MHz, and the delay was 0.248 seconds. Based on these findings, the difference in resource usage on the ESP32 before and after implementing TLS is concluded to be not significantly impactful. Keywords: IoT, MQTT, AES, RAM, CPU